2018
DOI: 10.1590/rbz4720170015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different vitamin D3 metabolites on intestinal calcium homeostasis-related gene expression in broiler chickens

Abstract: -The purpose of this study was to investigate the effects of vitamin D 3 metabolites 1α-hydroxycholecalciferol (1α(OH)D 3 ), 25-hydroxycholecalciferol (25(OH) 2 D 3 ), and 1,25-dihydroxycholecalciferol (1,25(OH) 2 D 3 ) on growth performance, bone quality, and intestinal calcium homeostasis-related gene expression in broiler chickens. One-day-old broilers were fed a basal diet and basal diet containing different vitamin D 3 metabolites. The body weight, feed intake, and feed conversion ratio in control and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The right tibia bones of the 72 chickens were defrosted and broken into small pieces using pliers to enable faster drying. The method used for determining bone mineral composition followed the method described by Hsiao and co-workers [15]; however, the defatting of the sample was not performed due to minor differences reported in the bone mineral composition in the tibia samples, which was able to be determined with or without lipid extraction [16]. In addition, the lipid extraction procedure is a rate-limiting step, and the use of chemical solvents has environmental concerns [16].…”
Section: Bone Mineralizationmentioning
confidence: 99%
“…The right tibia bones of the 72 chickens were defrosted and broken into small pieces using pliers to enable faster drying. The method used for determining bone mineral composition followed the method described by Hsiao and co-workers [15]; however, the defatting of the sample was not performed due to minor differences reported in the bone mineral composition in the tibia samples, which was able to be determined with or without lipid extraction [16]. In addition, the lipid extraction procedure is a rate-limiting step, and the use of chemical solvents has environmental concerns [16].…”
Section: Bone Mineralizationmentioning
confidence: 99%
“…Additionally, during the starter phase, broilers' enzyme systems are not completely mature to perform hydroxylation in the liver, which does not affect the efficiency of already hydroxylated metabolites such as 25(OH)D 3 . Hsiao et al (2018) observed greater expression of calbindin and β-glucuronidase in the duodenum of 21-day-old broilers reared in thermal comfort when fed diets supplemented with 1,25(OH) 2 D 3 and 25(OH)D 3 , as compared to VitD 3 . In contrast, Vazquez et al (2018) observed no effect on the performance of broilers reared in thermal comfort in the period from 1 to 21 days when fed 25(OH)D 3 associated with VitD 3 .…”
Section: -Hydroxycholecalciferol As An Alternative To Vitamin D3 In D...mentioning
confidence: 83%
“…Cholecalciferol (D 3 ) is the common way of adding vitamin D 3 to diets. However, it is currently possible to use isoforms or vitamin D 3 metabolites in diets for broilers (Fritts & Waldroup, 2003;Garcia et al, 2013;Han et al, 2016;Hsiao et al, 2018;Tizziani et al, 2019). Following absorption, vitamin D 3 is hydroxylated in the liver, resulting in the formation of the 25(OH) D 3 metabolite, the main circulating form in blood, used as a vitamin D marker in animals (Arnold et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calbindin activity in chickens is regulated by 1,25(OH) 2 D 3 ( Hall and Norman, 1990 ; Ferrari et al., 1992 ). In comparison to vitamin D 3 at the same level of inclusion, dietary 25OHD 3 provided at a dosage of 69 μg/kg has been shown to lead to a greater increase in the expression of calbindin after 6 h ( Hsiao et al., 2018 ). Although the enzyme 1 α-hydroxylase is mainly expressed in renal cells, it is also expressed in muscle and macrophage cells ( Shanmugasundaram and Selvaraj, 2012 ), and its activity is known to cause the inhibition of Eimeria tenella replication (Morris and Selvaraj, 2014).…”
Section: Introductionmentioning
confidence: 99%